2019
DOI: 10.1177/2047487319878373
|View full text |Cite
|
Sign up to set email alerts
|

The link between diabetes and atherosclerosis

Abstract: Atherosclerosis is one of the main complications of diabetes involving multiple causative factors. Dysfunction of the vascular endothelium is a hallmark of most conditions that are associated with both diabetes and atherosclerosis. Although the pathological link between diabetes and atherosclerosis is well-established, better comprehension of the underlying mechanisms is of utmost importance to identify novel potential molecular targets. It is difficult to separate the effects of hyperglycaemia from those of o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
101
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 142 publications
(126 citation statements)
references
References 53 publications
1
101
0
2
Order By: Relevance
“…Inflammatory signals are at the basis of all chronic diseases, and they are often triggered by dysmetabolic conditions associated with aging, a process widely defined as inflammaging [51][52][53][54]. In an experimental model of prolonged hyperglycemia and cardiomyopathy, high levels of the metastasis-associated lung adenocarcinoma transcript-1 lncRNA (MALAT1) were reported [55].…”
Section: Non-coding Rna and Their Promoter Methylation In Cardiovascumentioning
confidence: 99%
“…Inflammatory signals are at the basis of all chronic diseases, and they are often triggered by dysmetabolic conditions associated with aging, a process widely defined as inflammaging [51][52][53][54]. In an experimental model of prolonged hyperglycemia and cardiomyopathy, high levels of the metastasis-associated lung adenocarcinoma transcript-1 lncRNA (MALAT1) were reported [55].…”
Section: Non-coding Rna and Their Promoter Methylation In Cardiovascumentioning
confidence: 99%
“…For instance, there is a growth of evidence that also showed a higher prevalence of arteriosclerosis in people with diabetes. In addition, numerous observational studies have found increased levels of the mediators of inflammation, such as C-reactive protein, interleukin-6 (IL-6), and plasminogen activator inhibitor 1, to name only a few, as major associative findings between diabetes and atherosclerosis (La Sala et al, 2019). Insulin resistance, a prominent feature of type 2 diabetes mellitus, has been demonstrated as an important risk factor for inducing atherosclerosis among the patients diagnosed with diabetes even in the absence of hyperglycemia (DeFronzo, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Several observational studies suggest that damages on vascular homeostasis are due to the impact of chronic hyperglycaemia. Likewise, higher levels of the mediators of inflammation, such as C-reactive protein (CRP), interleukin-6 (IL-6), plasminogen activator inhibitor 1 (PAI-1), are observed in diabetic patients suggesting a positive correlation between diabetes and atherosclerosis [3]. Type 2 diabetes is, however, more associated to cardiovascular co-morbidities and mortality comparing to the other types of diabetes mellitus [4,5].…”
Section: Introductionmentioning
confidence: 99%